(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article explores how the Soviet regime systematically suppressed the ideals of national independence in Central Asia, particularly in Uzbekistan, from the 1920s through the 1980s. It examines the destruction of the Jadid movement, the ideological imposition of Soviet internationalism, and the silencing of nationalist thought. Despite such repression, the study uncovers the persistence of independence ideals through underground literature, cultural resistance, and dissident networks. This research sheds light on how national identity survived under authoritarian rule and laid the groundwork for post-Soviet sovereignty